Glove Technique in Single-Port Access Laparoscopic Surgery: Results of an Initial Experience. (5th April 2012) - Livraghi, Lorenzo; Berselli, Mattia; Bianchi, Veronica; Latham, Lorenzo; Farassino, Luca; Cocozza, Eugenio
Abstract : Introduction . Single-incision laparoscopic surgery (SILS) is a virtually "scarless" technique. A retrospective analysis is performed to evaluate an initial experience of this surgical approach. Materials and Methods . From January 2010 to October 2011, SILS was considered as a minimally invasive approach to abdominal disease. The access was made by a standard wound protector and a size 6 glove. A series of little accesses were made on the tips of the glove-fingers to induce pneumoperitoneum and to create a working channel for the laparoscopic instruments. An analysis of costs of this technique was made too. Results . SILS was successfully completed with low cost in 34 patients: 20 appendectomy, 12 cholecystectomy, and 2 right colectomy were performed with a median operative time of 35, 45, and 67.5 minutes, respectively. In no patient any conversion to standard laparoscopy or to open surgery was needed. The postoperative course was uneventful in all patients. In right hemicolectomy, the oncological parameters were respected. Conclusions . In this paper the glove-port technique showed multiple advantages. The SILS is a feasible approach for some pathologies in selected patients. The glove-port is a simple, low-cost, reproducible, and sure method to perform SILS in a high-experienced laparoscopic surgical centre.